MENGGALI POTENSI LOKAL KABUPATEN BANYUMAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA SD - Putri Handayani; Merdhenita Restuti; Miftakhul Jannah; Katrina Ramadhani; Ellianawati Subali; Wiwi Isnaeni (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study was to determine the application of the Project Based Learning (PjBL) learning model with ethnoscience to the improvement of creative thinking skills in the process of making tempe. The subjects in this study were 40 students in one school in Banyumas district. This type of research is quantitative research. The research method used one group pre-test and post-test design. Based on the results of the analysis obtained data pre-test and post-test creative thinking skills with a n-gain score of 0.7 with a high category. The results of the questionnaire for creative thinking skills were 14 students in the high category, 23 students in enough categories, and 3 students in the low category. It can be concluded that learning using the ethnics-charged Project Based Learning (PjBL) model can improve student's creative thinking skills in elementary schools.